Identification D’un Substrat Adequat Pour La Germination Du Fuzz De Canne A Sucre (Saccharum officinarum L.) A Ferkessedougou - Marcos Zadi; Louise Turquin; Crépin Pene (European Scientific Journal, ESJ, 2018)
An alternative solution to the importation of high performing varieties, integrating the importation of sugar cane fuzz, and the germination of these followed by a selection would be the beginning of a response to the low competitiveness of Ivorian sugar. In order to identify a substrate for fuzz germination and plant growth, three substrates (TKS1, Biofertil and Ecume) were tested in a 4-repeat blocks factorial device. The TKS1 recognized as effective for the germination of fuzz served as a control. The substrates were compared according to their effects on emergence dynamics, the rate,velocity andtime limit of germination of the SP70 1006 and VMC 96/56 fuzz. The results showed that Biofertil (0.83 ± 0.79 p.c.) and TKS1 (0.9 ± 0.94 p.c.) generated statistically identical germination rates. It is the same for the germination rate where these two substrates had similar effects, respectively 1.11 ± 1.06 fuzz/dand 1.19 ± 1.26fuzz/d. For these two parameters of germination, scum with respectively 0.4 ± 0.83 % and 0.53 ± 0.51 fuzz/dwas less efficient than the two previous substrates. Biofertil could therefore replace TKS1 under the conditions of Ferkessédougou 2.